A Study on the Uses of Green Manufacturing in Various Industries (International Journal of Innovative Research in Engineering & Management, 2021)
Manufacturing of "green" products, especially those utilized in  renewable energy systems and clean technology equipment of  all kinds. The “greening” of industry is accomplished by  reducing renewable resource consumption, recycling and  reusing trash, and decreasing emissions to minimize noise and  waste. This article offers an overview of green manufacturing,  including its overview and why it is needed, as well as green  manufacturing methods that reduce waste and emissions. The  present work focuses on ecological design for the environment,  including energy efficiency and product production with  reduced pollution. Further, author stresses the use of green  manufacturing to produce a cleaner product that can be reused,  resulting in a shorter product life cycle. An effort has been made  to speak about sustainability accounting as well as green supply  chain management. The main goal of green production is to  preserve the planet while simultaneously reducing the product's  quality.
Keywords: Emissions; Environment; Manufacturing; Technology; Pollution